Controlled Growth of SrxBa1−xNb2O6 Hopper‐ and Cube‐Shaped Nanostructures by Hydrothermal Synthesis. Issue 42 (30th April 2020) - Grendal, Ola G.; Nylund, Inger‐Emma; Blichfeld, Anders B.; Tominaka, Satoshi; Ohara, Koji; Selbach, Sverre M.; Grande, Tor; Einarsrud, Mari‐Ann
Abstract: Controlling the shape and size of nanostructured materials has been a topic of interest in the field of material science for decades. In this work, the ferroelectric material Sr x Ba1− x Nb2 O6 ( x= 0.32–0.82, SBN) was prepared by hydrothermal synthesis, and the morphology is controllably changed from cube‐shaped to hollow‐ended structures based on a fundamental understanding of the precursor chemistry. Synchrotron X‐ray total scattering and PDF analysis was used to reveal the structure of the Nb‐acid precursor, showing Lindqvist‐like motifs. The changing growth mechanism, from layer‐by‐layer growth forming cubes to hopper‐growth giving hollow‐ended structures, is attributed to differences in supersaturation. Transmission electron microscopy revealed an inhomogeneous composition along the length of the hollow‐ended particles, which is explained by preferential formation of the high entropy composition, SBN33, at the initial stages of particle nucleation and growth. Abstract : Take shape : Controlling the shape and size of nanostructured materials has been a topic of interest in the field of material science for decades. Here Sr x Ba1− x Nb2 O6 ( x= 0.32–0.82, SBN) was prepared by hydrothermal synthesis, and the morphology is controllably changed from cube‐shaped to hollow‐ended structures based on a fundamental understanding of the precursor chemistry.